Does my model predict a forward guidance puzzle? - Christopher G. Gibbs; Nigel McClung (Bank of Finland, 2019)
We provide suffcient conditions for when a rational expectations structural model predicts bounded responses of endogenous variables to forward guidance announcements. The conditions coincide with a special case of the well-known (E)xpectation-stability conditions that govern when agents can learn a Rational Expectations Equilibrium. Importantly, we show that the conditions are distinct from the determinacy conditions. We show how the conditions are useful for diagnosing the features of a model that contribute to the Forward Guidance Puzzle and reveal how to construct well-behaved forward guidance predictions in standard medium-scale DSGE models.
URN:NBN:fi:bof-201909101452
Keywords: E31; E32; E52; D84; D83; 330